Does Critical Thinking Mean Cultural Thinking? Using Language To Learn And Develop Character - Floriasti, Tri Wahyuni (Journal of English and Education (JEE), 2011)
One of the most widely discussed concepts in education and educational reform these days is critical thinking. This thing we call critical thinking or analysis has strong cultural components. An area of cultural difference that may influence critical thinking is the use of language to effect thinking and learning. It is more than just a set of writing and thinking techniques- it is a voice, a stance, a relationship with texts and family members, friends, teachers, the media, even the history of one's country (Fox, 1994, p.125). Critical thinking begins when people make the connections between their individual lives and social conditions. In classrooms that feature critical thinking, students are encouraged to participate actively, raising issues of concern in their daily lives, such as work, school, and housing as topics for class discussion. As teachers and scholars grow to understand the unique characteristics of the culture, it is important to see, observe, analyze and response appropriately through language in the class and social life so that young generation can learn how to appreciate members of another culture and go hand in hand with them. It may become an effort to shape the civil society. This condition does not stop at that step. It leads them to act and response critically in daily life. Then, this beneficial actions form good characters